Regulasi Konten Online dan Dampaknya terhadap Hak Kebebasan Berbicara di Platform Digital di Indonesia - Khulaili Harsya, Rabith Madah; Wamafma, Filep; Sakmaf, Marius Supriyanto; Triyantoro, Andri (Eastasouth Institute, 2024)
This study examines the regulation of online content and its impact on the right to freedom of speech on digital platforms in Indonesia, utilizing a juridical normative analysis. With the rapid growth of digital platforms, concerns over the balance between regulating harmful content and safeguarding free expression have intensified. The research explores the legal frameworks governing online content in Indonesia, analyzing how these regulations align with constitutional guarantees of freedom of speech. The findings reveal significant tensions between state interests in maintaining public order and individual rights to free expression, highlighting the potential for regulatory overreach and the chilling effect on public discourse. The study underscores the need for a more balanced approach to content regulation, advocating for clearer legal guidelines and independent oversight to ensure that regulations do not undermine democratic principles. This research contributes to the ongoing debate on the legal and ethical dimensions of content regulation in the digital age, offering insights for policymakers, legal practitioners, and digital platform operators.